Temperature stress and its impact on bivalve mortality: A review of physiological responses - Pourmozaffar S.; Tamadoni Jahromi S.; Pazir M.Kh.; Behzad Sarvi; Amini Khoei Z.; Noora Barzkar; Behzadi S.; Nahavandi R.; Adeshina I. (Green Wave Publication, 2025)
Temperature significantly influences the distribution and survival of bivalve populations, with elevated temperatures resulting in increased mortality rates. Research indicates that temperature fluctuations can markedly affect bivalve immune responses, including gene expression, hemocyte concentrations, and overall immunocompetence. Higher temperatures impair immune functions, leading to decreased phagocytic activity, compromised immune parameters, and disrupted metabolic processes, which collectively contribute to increased mortality. Understanding the relationship between temperature stress and bivalve survival is crucial for effective population management and for developing strategies to mitigate the negative impacts on bivalve populations in changing ecosystems.